2006
DOI: 10.1007/s11325-006-0076-8
|View full text |Cite
|
Sign up to set email alerts
|

Nightmares and oxygen desaturations: is sleep apnea related to heightened nightmare frequency?

Abstract: In the 19th century, several authors held the view that nightmares are caused by oxygen shortage. The present study was designed to study nightmare frequency in patients with obstructive sleep apnea syndrome and its relationship to respiratory parameters. A brief questionnaire was administered to 323 patients with sleep apnea syndrome before their first laboratory night. The reduction in nightmare frequency in the sleep apnea group was explained by the reduced dream recall frequency. Despite some illustrative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 25 publications
3
29
0
2
Order By: Relevance
“…In a student sample, snoring was not related to nightmare frequency [7]. Schredl et al [25], on the other hand, found a decreased nightmare frequency in OSAS patients compared with healthy controls, a finding that is likely explained by the lower DRF in this sample.…”
Section: Traumerinnerungshäufigkeit Und Alptraumhäufigkeit Bei Patienmentioning
confidence: 48%
See 1 more Smart Citation
“…In a student sample, snoring was not related to nightmare frequency [7]. Schredl et al [25], on the other hand, found a decreased nightmare frequency in OSAS patients compared with healthy controls, a finding that is likely explained by the lower DRF in this sample.…”
Section: Traumerinnerungshäufigkeit Und Alptraumhäufigkeit Bei Patienmentioning
confidence: 48%
“…When the effect of current stress (subjective stress measured via questionnaire) was controlled statistically, the difference in DRF between sleep apnea patients and healthy controls was no longer significant, indicating that psychological factors might explain the findings since there was no significant correlation with symptom severity [respiratory disturbance index (RDI), oxygen saturation nadir]. Whereas Schredl et al [23] also reported heightened DRF in OSAS patients, Schredl et al [25], in a large sample (N=309), found a reduction in DRF. Interestingly, Carrasco et al [2] reported a decrease in dream recall percentage after induced REM awakenings during continuous positive airway pressure (CPAP) treatment nights in comparison to the REM awakening nights prior to therapy, despite the well-known REM rebound effect.…”
Section: Traumerinnerungshäufigkeit Und Alptraumhäufigkeit Bei Patienmentioning
confidence: 96%
“…For a follow-up study, it would be interesting to elicit all diagnoses of the patients since, for example, it has been shown that comorbid depression correlates with nightmare frequency in patients with sleep apnea. 18,19 The finding that age and gender is not related to the "telephone counselling" variable also supports the notion that the primary diagnosis for admission to the sleep lab might not be the main influencing factor since men more often undergo diagnostic procedures for sleep-related breathing disorders and younger persons more often for different types of hypersomnia; for age and gender distribution in German sleep centers, see Schredl et al…”
Section: Discussionmentioning
confidence: 63%
“…A detailed study of the relationship between arousals and REM sleep parameter was not performed, and the automatic analysis of routine diagnostic procedures are not valid. In addition, the AHI and oxygen saturation are a rough measure for the number of relevant desaturations per night 12 .…”
Section: Osahsmentioning
confidence: 99%
“…The Obstructive Sleep Apnea and Hypopnea Syndrome (OSAHS) is characterized by the deposition of the tongue in the side walls of the oropharynx and soft palate, which promotes a collapse of these structures and reduction or absence decreased oxygenation would have an increased prevalence of nightmares, but respiratory parameters in patients with OSAHS showed that they did not correlate significantly with the frequency of nightmares 12 .…”
Section: Introductionmentioning
confidence: 99%